Waiting for the real dragon: How globalization, patriotism and trust shape tolerance in Southeast Asia. Issue 2 (June 2017) - Collet, Christian
Southeast Asia is the world's most diverse and rapidly modernizing region, yet one where modernization theory is challenged (e.g. Bell et al., 1995) and where allegiance to authoritarian regimes appears trenchant (Chang et al., 2013; Dalton and Shin, 2014). Using the AsiaBarometer, I consider the influence of modernization and allegiance on potential democratization by analyzing an established indicator of assertive change: tolerance of homosexuality (Inglehart and Welzel, 2005: Ch. 5, forthcoming). The findings reveal differences between Southeast Asians and the West and between citizens in the Sinic and Indic subregions. Exposure to foreign cultures produces a significant increase in tolerance among Sinicized citizens, but has no meaningful effect on those in Indic states. Patriotism and trust in civil society also boost tolerance among Sinicized citizens, but reduce the probability of tolerance among citizens in Indic states. The strong linkage between sexual tolerance and gender equality driven by social factors and secularism in the West does not manifest in Southeast Asia. While the findings suggest potential for change in the Sinicized region, they underscore the different effects that globalization and allegiance may have on citizens living under Southeast Asia's variety of regimes.